Rapid prototyping-coded masks for x-ray backscatter imaging - Munoz, Andre Arelius Marcus; Vella, Anna; Healy, Matthew J. F.; Lane, David W. (Cranfield University, 2018)
Coded masks (CM) often lack a self-supporting structure that is difficult to manufacture without recourse to drilled holes in place of ideal square apertures, degrading imaging properties. An alternative approach is presented with three-dimensional (3-D) printed CM molds cast with a radio-opaque material that allows square elements to be retained. Two methods are presented; hot casting a bismuth alloy (density 8.6  g cm  −  3) and cold casting with tungsten powder/epoxy resin (densities 9.6 and 10.6  g cm  −  3). A critical review of 3-D printed-CM fabrication along with some typical x-ray backscatter images is presented. A signal-to-noise ratio from both the machined tungsten and cold cast 3-D printed mask were comparable, with the former having a slight advantage. Also, 3-D printed cold cast masks were found to be more economical and easier to rapid prototype over traditional drilled tungsten masks.
Keywords: coded apertures; coded masks; x-ray backscatter; three-dimensional printing